Reflecting the 2018 History Ministerial Task Team Report on compulsory History in South Africa (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The History Ministerial Task Team Report (MTT), published in February 2018, has been awaited by educators of History in South Africa for them to be informed on thoughts, trends and statuses of compulsory History Education in schools globally. Educators also hoped to be informed about other important aspects of History education, such as educators’ impressions of the 2011 Curriculum and Assessment Policy Statement (CAPS) for History and possibilities for revision. Other concerns on the table included the field of teacher training, as well as the financial and logistical implications of transforming History teaching into a compulsory subject. The major purpose of this paper is to reflect on the History MTT’s discussion of the status of, specifically, compulsory History in Africa and further afield, and to establish whether the MTT’s report can in this regard serve as a reliable indicator for making any informed decision on whether History Educationin South African schools should indeed be compulsory up to the Grade 12 level. The authors contest the quality of the research conducted by the History MTT pertaining to compulsory History in other countries, which in turn questions the reliability of the Report in its entirety, but which unfortunately cannot be afforded attention in this paper due to lack of space. Given this contestation on quality pertaining to the first section of the History MTT report, the authors make some observations and propose recommendations to the Department of Basic Education, who commissioned the History MTT. The essence thereof is to strongly suggest that much more thorough research should be conducted than that received by the DBE in this Report, to ensure more responsible considerations and points of departure than those currently unfolding.
Keywords: History Education; The History Ministerial Task Team Report (MTT); Compulsory History; Department of Basic Education; Historical method